2011
DOI: 10.1159/000335661
|View full text |Cite
|
Sign up to set email alerts
|

Adult Phenotypes in Angelman- and Rett-Like Syndromes

Abstract: ID of unknown etiology. Results: We describe the evolution of the phenotype in adults with EHMT1, TCF4, MECP2, CDKL5, and SCN1A mutations and 22qter deletions and also provide an overview of previously published adult cases with similar diagnoses. Conclusion: These data are highly valuable in adequate management and follow-up of patients with Angelman-and Rett-like syndromes and accurate counseling of their family members. Furthermore, they will contribute to recognition of these syndromes in previously undiag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 103 publications
1
23
0
1
Order By: Relevance
“…Cdkl5 -/y mice display hyperactivity, motor defects, reduced anxiety, decreased sociability, and impaired learning and memory. These phenotypes have been described in other ASD and RTT mouse models (2, 16, 17, 19, 26) and may mimic the absence of hand skills, intellectual disability, hyperactivity, and poor response to social interactions that have been described in CDKL5 patients (12,41). While video-EEG monitoring revealed an absence of spontaneous seizures in Cdkl5 -/y mice, ERP analysis showed attenuated and delayed ERP polarity peaks suggestive of impaired neuronal connectivity, which is consistent with findings in ASD and RTT patients (30,31) and animal models (19,28,29).…”
Section: Discussionmentioning
confidence: 76%
“…Cdkl5 -/y mice display hyperactivity, motor defects, reduced anxiety, decreased sociability, and impaired learning and memory. These phenotypes have been described in other ASD and RTT mouse models (2, 16, 17, 19, 26) and may mimic the absence of hand skills, intellectual disability, hyperactivity, and poor response to social interactions that have been described in CDKL5 patients (12,41). While video-EEG monitoring revealed an absence of spontaneous seizures in Cdkl5 -/y mice, ERP analysis showed attenuated and delayed ERP polarity peaks suggestive of impaired neuronal connectivity, which is consistent with findings in ASD and RTT patients (30,31) and animal models (19,28,29).…”
Section: Discussionmentioning
confidence: 76%
“…The two first studies reported the same family with two affected brothers with PMS (Verhoeven et al, 2012;Willemsen et al, 2012). Until the age of 17, the development of the younger brother was marked by the severity of the ID and hyperactivity together with temper tantrums and absence of language.…”
Section: Shank and Bipolar Disordermentioning
confidence: 97%
“…Apart from these 3 genes, there are at least 28 OMIM morbid genes (https://www.omim.org/) described in literature in which variants may cause gene disorders/syndromes with overlapping Rett-like phenotypes ( Table 2). 9,10,14,[36][37][38] Some of these genes are associated with well-known syndromes such as Pitt-Hopkins syndrome (TCF4, Among the patients, without deficiencies in 1 of these 3 genes (n = 35), pathogenic sequence variants were identified in SCN2A…”
Section: Many Genes Many Disordersmentioning
confidence: 99%
“…,61 Kleefstra syndrome is caused by 9q34.3 microdeletions including EHMT1 or sequence variants of this gene. 60 EHMT1 variants have not yet been reported in patients with a Rett-like phenotype, but have great phenotypic overlap and has been linked to the Rett-like spectrum 36. …”
mentioning
confidence: 99%